2008
DOI: 10.1021/jp709825y
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Catalyst Particles in CCVD Synthesis of Multiwalled Carbon Nanotubes Revealed by the Cooling Step Study

Abstract: The true chemical nature and physical state of the catalyst particles in Catalytic Chemical Vapor Deposition (CCVD) synthesis of carbon nanotubes are the subject of intense discussions, as it is one of the keys to understand their growth mechanisms. The CCVD method considered in this article involves pyrolysis of mixed liquid aerosols and leads to the synthesis of large carpets of multiwalled nanotubes (MWNTs) partially filled with iron-based materials. The experimental approach consists in studying the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 43 publications
(91 reference statements)
4
41
0
Order By: Relevance
“…However, such oxide phases are not the catalytic phases in the process we use, where nanoparticles giving rise to CNT growth were shown to be cementite nanoparticles [22]. We have shown that the occurrence of oxides is due to iron oxidation during the cooling step [15], and the present results indicate that the oxidation is not complete for all iron-based particles since Fe 3 O 4 is detected. In addition, in our study no oxygen-containing promoters such as traces of water have been added to the reactive gas phase.…”
Section: Methodsmentioning
confidence: 58%
See 4 more Smart Citations
“…However, such oxide phases are not the catalytic phases in the process we use, where nanoparticles giving rise to CNT growth were shown to be cementite nanoparticles [22]. We have shown that the occurrence of oxides is due to iron oxidation during the cooling step [15], and the present results indicate that the oxidation is not complete for all iron-based particles since Fe 3 O 4 is detected. In addition, in our study no oxygen-containing promoters such as traces of water have been added to the reactive gas phase.…”
Section: Methodsmentioning
confidence: 58%
“…For this sample grown during the early stages and thus exhibiting a low amount of carbon, Raman spectroscopy is sensitive to both iron-based and carbon phases whereas XRD is mainly sensitive to iron-based phases. mass ratio = 4/3, figure 2 (e)) [11,15]. This is the first XRD identification of α-Fe 2 O 3 in such samples, due probably to a too low content of such phase in previous studies [11,15,17,19].…”
Section: Methodsmentioning
confidence: 62%
See 3 more Smart Citations